Vasa vasorum of proximal cerebral arteries after dural crossing — potential imaging confounder in diagnosing intracranial vasculitis in elderly subjects on black-blood MRI - Guggenberger, Konstanze Viktoria; Torre, Giulia Dalla; Ludwig, Ute; Vogel, Patrick; Weng, Andreas Max; Vogt, Marius Lothar; Fröhlich, Matthias; Schmalzing, Marc; Raithel, Esther; Forman, Christoph; Urbach, Horst; Meckel, Stephan; et al. (European radiology, 2022)
Objectives Vessel wall enhancement (VWE) may be commonly seen on MRI images of asymptomatic subjects. This study aimed to characterize the VWE of the proximal internal carotid (ICA) and vertebral arteries (VA) in a non-vasculitic elderly patient cohort. Methods Cranial MRI scans at 3 Tesla were performed in 43 patients (aged ≥ 50 years) with known malignancy for exclusion of cerebral metastases. For vessel wall imaging (VWI), a high-resolution compressed-sensing black-blood 3D T1-weighted fast (turbo) spin echo sequence (T1 CS-SPACE prototype) was applied post gadolinium with an isotropic resolution of 0.55 mm. Bilateral proximal intradural ICA and VA segments were evaluated for presence, morphology, and longitudinal extension of VWE. Results Concentric VWE of the proximal intradural ICA was found in 13 (30%) patients, and of the proximal intradural VA in 39 (91%) patients. Mean longitudinal extension of VWE after dural entry was 13 mm in the VA and 2 mm in the ICA. In 14 of 39 patients (36%) with proximal intradural VWE, morphology of VWE was suggestive of the mere presence of vasa vasorum. In 25 patients (64 %), morphology indicated atherosclerotic lesions in addition to vasa vasorum. Conclusions Vasa vasorum may account for concentric VWE within the proximal 2 mm of the ICA and 13 mm of the VA after dural entry in elderly subjects. Concentric VWE in these locations should not be confused with large artery vasculitis. Distal to these segments, VWE may be more likely related to pathologic conditions such as vasculitis. Key Points • Vasa vasorum may account for concentric VWE within the proximal 2 mm of the ICA and 13 mm of the VA after dural entry in non-vasculitic elderly people. • Concentric enhancement within the proximal 2 mm of the intradural ICA and within the proximal 13 mm of the intradural VA portions should not be misinterpreted as vasculitis. • Distal of this, VWE is likely related to pathologic conditions, in case of concentric VWE suggestive of vasculitis.